Investigating the relationship between marital adjustment and happiness of married women in Tabriz - Mahin Tafsileh; mahmoud elmi (فصلنامه زن و جامعه, 2021)
Happiness is also one of the most essential innate desires and psychological needs of man and marital adjustment as one of the most important factors affecting family functioning. The aim of this study was to determine the relationship between marital adjustment and happiness of married women in the fourth district of Tabriz. Research methods, survey and data collection tools were standard questionnaires. The statistical population was married women living in Tabriz that 205 samples were selected by systematic random sampling. The collected data showed that the average rate of marital adjustment was 57.04% and the average level of happiness was 59.17%. Significant tests showed that there is a significant direct relationship between marital adjustment (and its four dimensions) and happiness of married women in the fourth district of Tabriz. The greater the happiness, the greater the marital adjustment. Happiness is a ground for the psychological and social development of the couple and the improvement of marital relations and coping with psychological and social pressures.